Effect of Dhikr on Blood Pressure in Pregnant Women with Hypertension - Sari, Dian Nirmala; Djamil, Masrifan; Suwandono, Agus (Indonesian Journal of Medicine, 2020)
Background: Hypertension is a 5-10% of complications in pregnancy and is one of the most common causes of death besides bleeding and infection, and also contributes to the morbidity and mortality of pregnant women. The purpose of this study was to examine effect of dhikr on blood pressure in pregnant women with hypertension.Subjects and Method: This was an experimental study conducted in Banjarnegara district health center, Central Java, in June 2018. A sample of 30 pregnant women with hypertension was selected for this study randomly. The dependent variable was blood pressure. The independent variable was dhikr. Blood pressure was measured by sphygmomanometer. Mean difference between of systolic and diastolic blood pressure in two groups after intervention was tested by t test.Results: After intervention, diastolic blood pressure in the intervention group (Mean= 136.67; SD= 6.17) was lower than in the control group (Mean= 141.33; SD= 5.16), and it was statistically significant (p= 0.006). After intervention, diastolic blood pressure in the intervention group (Mean= 88.67; SD= 3.52) was lower than in the control group (Mean= 92.00; SD= 4.41), and it was statistically significant (p= 0.025).Conclusion: Dhikr decreases blood pressure in pregnant women with hypertension.Keywords: blood pressure, hypertension, pregnant womenCorrespondence: Dian Nirmala Sari. Applied Midwifery, Graduate Program, School of Health Polytechnics, Ministry of Health Semarang. Jl. Tirto Agung, Pedalangan, Banyumanik, Kota Semarang 50268, Central Java, Indonesia. Email: nirmalasaridian@yahoo.co.idIndonesian Journal of Medicine (2020), 05(01): 87-94https://doi.org/10.26911/theijmed.2020.05.01.12